Developments in Glycopeptide Antibiotics - Blaskovich, Mark A. T; Hansford, Karl A; Butler, Mark S; Jia, ZhiGuang; Mark, Alan E; Cooper, Matthew A (ACS infectious diseases, 2018)
Glycopeptide antibiotics (GPAs) are a key weapon in the fight against drug resistant bacteria, with vancomycin still a mainstream therapy against serious Gram-positive infections more than 50 years after it was first introduced. New, more potent semisynthetic derivatives that have entered the clinic, such as dalbavancin and oritavancin, have superior pharmacokinetic and target engagement profiles that enable successful treatment of vancomycin-resistant infections. In the face of resistance development, with multidrug resistant (MDR) S. pneumoniae and methicillin-resistant Staphylococcus aureus (MRSA) together causing 20-fold more infections than all MDR Gram-negative infections combined, further improvements are desirable to ensure the Gram-positive armamentarium is adequately maintained for future generations. A range of modified glycopeptides has been generated in the past decade via total syntheses, semisynthetic modifications of natural products, or biological engineering. Several of these have undergone extensive characterization with demonstrated in vivo efficacy, good PK/PD profiles, and no reported preclinical toxicity; some may be suitable for formal preclinical development. The natural product monobactam, cephalosporin, and β-lactam antibiotics all spawned multiple generations of commercially and clinically successful semisynthetic derivatives. Similarly, next-generation glycopeptides are now technically well positioned to advance to the clinic, if sufficient funding and market support returns to antibiotic development.